Integrated Control of Motion and Contactless Power Transfer for Doubly-Fed Induction Machines in Complex Rotary Apparatuses. Issue 1 (July 2017) - Tilli, Andrea; Bosso, Alessandro; Conficoni, Christian; Hashemi, Ahmad
Abstract: A novel control solution for Doubly-Fed Induction Machines is proposed to enable new applications of such kind of machines. This strategy guarantees a fully decoupled motion control and contactless power transfer between stator and rotor, by using controlled inverters on both stator and rotor side. For large and complex rotary apparatus with relevant electric loads and actuators placed on-board the mobile part, the proposed solution allows to exploit direct-drive versions of Doubly-Fed Induction Machines for both moving and feeding independently the rotating part, where the rotor-side converter has to be hosted. Power transfer is attained through two different working principles in order to achieve decoupling from the torque references and to suitably deal with voltage saturations on power converters. Global asymptotic stability proof is provided for this control strategy. Simulation results are reported in order to validate the promising theoretical developments.